Detection of Isocitrate Dehydrogenase (IDH-1), Epidermal Growth Factor Receptor (EGFR), P53 and C-erbB2/HER2 mutation in glial tumour - Azman, Nusaibah; Mat Zin, Anani Aila; Tuan Sharif, Sharifah Emilia; Bakrin, Ikmal Hisyam (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: In the last decade, several molecular pathways in gliomagenesis have been discovered, with each involving a unique set of molecular alterations. IDH1 has become a diagnostic tool in the latest 2016 WHO Clas- sification. The tumour protein, p53, is involved in the IDH-mutant arm, observed in astrocytoma and oligodendro- glioma (grades II and III), and secondary glioblastoma. Meanwhile, EGFR and c-erbB2/HER2 were postulated to be expressed in higher-grade glioma as the disease progresses. Methods: A retrospective cross-sectional study was conducted to evaluate the association of IDH1, EGFR, p53 and c-erbB2/HER2 protein expression in astrocytic and oligodendroglial tumours with clinicopathological data in HUSM, Kota Bharu, Kelantan, Malaysia. This study ex- amined 61 archived formalin-fixed paraffin-embedded (FFPE) tissue blocks of patients diagnosed with glioma. The immunohistochemistry (IHC) test was performed using antibodies, IDH1, EGFR, p53 and c-erbB2/HER2, and the protein expressions were evaluated microscopically. Finally, the association between IDH1, p53, EGFR and c-erbB2/ HER with the clinicopathology variables were statistically analysed. Results: A total of 61 glioma cases consisting of 36 (59%) males and 25 (41%) females were included in this study. The IDH1 protein was positively expressed in 14 cases (23%), P53 was highly expressed in 26 cases (42.6%), and EGFR was substantially observed in 34 cases (55.7%). For glioblastoma cases, IDH1 was expressed in two cases (11.1%), EGFR in 14 cases (77.7%), p53 in 12 cases (66.7%) and c-erbB2 in 1 case (5.6%). Significant associations exist between IDH1, p53 and EGFR expressions in astrocytoma and oligodendroglial tumours with the histological types and WHO tumour grades. Conclusion: Re- cently, our knowledge regarding the genetics of central nervous system (CNS) tumors has expanded; hence, newer antibodies or molecular markers, which can be used in IHC, are continuously being developed. These antibodies, IDH1, p53 and EGFR markers are useful for diagnostic, prognostication and therapeutic. In addition, help to clarify the nature of cellular maturation, tissue differentiation, and tumor progression to be considered as an integral part of WHO classification of CNS tumours.